Where duty lies a New Brunswick soldier in the trenches of World War I - Cunningham, John 1939- (Pottersfield Press, 2018)
"This is the story of how 23-year-old Frank Grimmer from St. Andrews, New Brunswick, ended up in the mud of Passchendaele under heavy artillery fire constructing supply lines that supported the Canadian advance during the Third Battle of Ypres. Here he found himself often deprived of the guns and ammunition to advance or defend himself. In the hours leading up to the launch of the Canadian assault on Passchendaele Ridge, Frank, thrown several yards by an artillery blast, went on to do all in his power to "render aid" to the wounded and those who died. His bravery earned him the Military Medal - and a thousand nights of torment remembering the violence of the events."--
Keywords: Schlacht um Flandern -- 1917; Soldat; New Brunswick; Grimmer, Frank; World War (1914-1918); Ypres, 3rd Battle of (Ieper, Belgium : 1917); Ypres, 3rd Battle of, Ieper, Belgium, 1917; Soldiers / New Brunswick / Biography; World War, 1914-1918 / Canada; HISTORY / World; Soldiers; Belgium / Ieper; Canada; 1914-1918; Biography; Biografie